A latent form of essential thrombocythemia presenting as portal cavernoma - Cai, Xiao-Yan (The WJG Press and Baishideng, 2009)
Essential thrombocythemia is frequently associated with abdominal thrombotic complications including portal cavernoma as a consequence of chronic portal vein thrombosis. Essential thrombocythemia in a latent form is difficult to identify at onset due to the absence of an overt disease phenotype. In the presented case report, the diagnosis of essential thrombocythemia was initially missed because the typical disease phenotype was masked by bleeding and hypersplenism. The correct diagnosis was only reached when the patient experienced persistent thrombocytosis and pseudohyperkalemia after a shunt operation.